Entre temps collectif et temps individuel, les espaces de la pêche à la ligne. Issue 2 (4th May 2019) - Guillaume, Olivier
Abstract : With a comparison of several amateur angling techniques, this contribution shows that fishing activities are not limited to solitary practice or small groups. Moreover, fishermen's conceptions of time and space do not solely consist of reclaiming for oneself a time and a space freed from constraints. Interviews and observations carried out in different places and with enthusiasts practicing various fishing techniques show that this leisure activity links collective and public activities with more private individual activities. Dedicated to the transmission of knowledge based on methods used by trade guilds as well as the setting up of community links, the collective activities take place in constricted and wintry spaces, and then in spring spaces with the start of the fishing season. As the fishing trips are individual in nature and situated in mobile or fixed spaces, they allow the fishermen the opportunity for introspection while fostering an intimate relationship with the animal, based on domination and comfort. The fishing trips also offer the fishermen the possibility to construct themselves as an autonomous subject. If the institutionalization and the intensity of the collective and individual fishing activities depend on the complexity of the techniques applied, their coordination allows the fishermen to constitute themselves as members of a community and as autonomous subjects.